Acute neurophysiologic effects of botulinum toxin type A intramuscular injection on extensor digitorum brevis muscle in healthy adults. (May 2022) - Boulias, Chris; Ismail, Farooq; Phadke, Chetan P.
Abstract: Introduction: Anecdotal clinical experience shows that patients often indicate that their spasticity improves on the day of treatment with intramuscular botulinum injection. Previous research shows that compound motor action potentials (CMAPs) decrease 48 h post-injection. However, no studies to date have assessed the neurophysiological changes less than 48 h post-injection. Methods: Fifteen healthy control subjects (10 F; mean age 41 ± 11 years) participated in this randomized double-blind study. We injected 10 units of either onabotulinumtoxinA or incobotulinumtoxinA in the extensor digitorum brevis (EDB) muscle, one in each foot. We performed serial CMAP assessments using nerve conduction study of the peroneal nerve at following time intervals after botulinum injection – 2, 4, 6, 24, 26, 28, 30, 48, 72 h and 6 days post-injection. We used an ANOVA with repeated measures separately for each type of toxin. Results: Post-hoc tests using the Bonferroni correction revealed that there was a statistically significant decrease in the mean EDB CMAP amplitude from baseline starting at 24 h post-injection in the incobotulinumtoxinA group (p < 0.05) and 4 h post-injection in the onabotulinumtoxinA group (p < 0.05). Conclusion: We conclude that both toxin formulations tested in this study exert a significant decrease in EDB CMAP amplitude in the period of <48 h post-injection. Highlights: We injected two formulations of botulinum toxin in the extensor digitorum brevis muscle of healthy subjects. Botulinum toxin injection produced a significant decrease in compound motor action potential up to 4-h post-injection. We did not test changes in muscle strength after botulinum toxin injections. The relationship between changes in compound motor action potential and muscle strength remains unknown. Future studies need to assess neurophysiologic changes hours after botulinum toxin injections in patients with spasticity.